Comparative Analysis of Online Gambling Laws and Implications on The Sustainability of the SDGs - Aliyyah Aprilia; Winsherly Tan; Tantimin (Faculty of Law, University of Merdeka Malang, 2026)
Online gambling is the one of impact the high poverty rate in Indonesia. This is an obstacle to sustainable development Government SDGs. This study formulates three main problems: related to the impact of online gambling on sustainable development, the implementation and enforcement of existing laws in Indonesia related to online gambling and comparisons regarding online gambling regulations in Indonesia, Malaysia and Singapore. Indonesia already has related regulations but their enforcement still faces challenges that cause poverty rates to continue to increase due to losses in online gambling games. This hinder the realization of sustainable development, the first element of which is “No Poverty”. Compared to Malaysia which strictly prohibits religious regulations and norms and Singapore which allows its people to gamble, Indonesia needs to carry out regulatory reform and maximum enforcement so that the negative impacts of online gambling do not further hinder sustainable development Government SDGs.